Design of a Cooper-Pair Box Electrometer for Application to Solid-State and Astroparticle Physics - Tosi, Leandro (2019)
We describe the design and principle of operation of a fast and sensitive electrometer operated at millikelvin temperatures, which aims at replacing conventional semiconducting charge amplifiers in experiments needing low back action or high sensitivity. This electrometer consists of a Cooper-pair box (CPB) coupled to a microwave resonator, which converts charge variations to resonance frequency shifts. By analyzing in detail its sensitivity to various parameters, we find that the resonator nonlinearity induced by the CPB can be exploited to improve sensitivity. Using conventional nanofabrication and measurement techniques, a charge sensitivity down to 10-7e/Hz with a megahertz bandwidth can be reached, which outperforms by 1 order of magnitude existing single-charge electrometers operated in the linear regime and opens up alternative possibilities in several fields such as mesoscopic and particle physics.